GENDER ROLE CONFLICT OF PASTORS’ HUSBANDS AT BATAK KARO PROTESTANT CHURCH - Karina Meriem Beru Brahmana (Universitas HKBP Nommensen, 2020)
The purpose of this study is to determine the gender role conflict of the pastor's husband in the Protestant Karo Batak Church (GBKP). This research method is quantitative by using the Gender Role Conflict Scale (GRCS) scale proposed by O'Neil, et al. (1986) used to measure gender role conflict and analyzed descriptively using the SPSS 24 program. The Gender-role Conflict Scale developed by O'Neil., et al (1986) has 37 items with 4 indicators namely Restricted Emotionality (RE), Restrictive Affectionate Behavior Between Men (RABBM), Success / Power / Competition (SPC), and Conflict Between Work and Family Relations (CBWFR). Based on the results of a pilot test measuring gender role conflict using Lisrel 8.50 it is known that of the 37 items of gender role conflict, 23 items were declared valid and 14 items were declared invalid with a reliability of 0.723. The results of statistical calculations show that the mean of gender role conflict is 89.10. Based on the results of the mean, it is known that in general gender role conflict in the pastor's husband GBKP is in the medium category because it is at a score of 89.10. In addition, from the four indicators it is known that the highest mean lies in the SPC of 35.53 followed by RE of 21.58, RABBM of 15.87 and finally CBWFR of 12.73.